Validity of Psammoperca datnioides Richardson 1848 and redescriptions of P. waigiensis Cuvier in Cuvier & Valenciennes 1828 and Hypopterus macropterus (Günther 1859) in the family Latidae (Perciformes) from the Indo-West Pacific - Iwatsuki, Yukio; Newman, Stephen J.; Tanaka, Fumiya; Russell, Barry C. (Zootaxa, 2018)
Psammoperca datnioides Richardson 1848, long considered a synonym of P. waigiensis (Cuvier in Cuvier & Valenciennes 1828), is redescribed as a valid species of Psammoperca Richardson 1848. The species is likely to be endemic to Australia, where it was formerly considered to be P. waigiensis, but differs from P. waigiensis in having the following characters: more slender body (mean depth 28.9% of SL vs. mean depth 36.7% of SL in P. waigiensis), pored lateral-line scales 49–54 (vs. 46–48 in P. waigiensis), scale rows above and below lateral line 6½ / 10½–11½ (vs 4½ / 9½–10½ in P. waigiensis), and vertical at hind margin of maxilla posterior/behind center of eye (vs. vertical at hind margin of maxilla anterior to/in front of hind margin of eye in P. waigiensis). Live specimens of Psammoperca datnioides have a uniformly dense black or brownish body, with this dark colour on body scales and pored lateral-line scales persisting even in preserved specimens. Live specimens of Psammoperca waigiensis have a brownish body, often golden in colour, and pored lateral-line scales that are yellow-edged. The COI sequence (cytochrome c oxidase subunit I, 612 bp) of P. datnioides also is distinct from P. waigiensis, and the related and poorly known Hypopterus macropterus (Günther 1859). The latter species is redescribed and diagnosed with eight indistinct dark bands on the head and body, and dorsal-fin rays VII-I, 14–15 (vs. no dark bands and dorsal-fin rays VII-I, 12–13 in Psammoperca). Nominal species in the genus Psammoperca are discussed and Cnidon chinensis Müller & Troschel 1849 (type locality: Manila, Philippines) is included as a junior synonym of P. waigiensis. Psammoperca vaigiensis Boulenger 1895 is an unneeded emendation and thus an invalid name. Psammoperca macroptera Günther 1859 is retained in the monotypic genus Hypopterus Gill 1861 in the family Latidae, although the species has been overlooked in most studies on the Latidae and/or Centropomidae. A key to the Latidae is provided.